Development of Natural Science Learning Models Based on Multiple Inteligences to Improve Higher Order Thinking Skills in Elementary Schools. Issue 4 (March 2020) - Acesta, Arrofa; Sumantri, M.Syarif; Fahrurrozi,
Abstract: This research is motivated by the learning of Natural Sciences which have not been integrated with multiple Intelligence and Higher order Thinking Skills (HOTS). The objectives of this study are:. 1) To describe the model of science learning based on multiple intelligences in elementary schools. 2) To describe the learning model of the effectiveness of multiple intelligence-based science in elementary schools. This study uses research or development research and development (R&D) methods, the research methods used to produce certain products, and tests the effectiveness of the products carried out by the research carried out, Design Based Research- Development Planning based on targets from Herington, McKenney, Reeves, Oliver Based on the research results that have been explained, the following conclusions are obtained.The validity of the science, environment, technology and community model based on the validity of the experts meets the valid criteria, the learning kit consisting of lesson plans and worksheets achieves valid. Practicality of science, environment, technology and society models based on practical assessment has reached practical criteria and assessment of students has reached very practical criteria. The effectiveness of the questionnaire appreciation for learning science using the model of science, environment, technology and society from all four aspects.